Learning Outcomes of Chinese Language Training for Binus University Employees - Agustian, Agustian (Humaniora, 2016)
This article discussed about the results of learning Chinese language for BINUS University employees. Learning method for adults and children are different, thus required teaching material and method that suit them. The aim of this research was to find out results of learning Chinese language through the material and teaching method used during training. The methods were descriptive qualitative, direct observation as trainer and collects participant test results as research data. The results show that teaching material is appropriate, however it needs to add review part. Direct method are used during the training makes the participants use Chinese language in daily conversation to achieve the goal of training. Indeed, it needs to strengthen mastery of participants’ basic Mandarin through explanation about using the vocabulary and adding the classroom activities.